Severe Pericardial Effusion Due to Autoimmune Hypothyroidism With Levothyroxine Withdrawal and Systemic Lupus Erythematosus - Israel, Sylvernon; Tan, Katherine Ann; Gomez, Ma. Felisse Carmen; Gan, Florence Rochelle; Uy-Ho, Jean (Journal of the ASEAN Federation of Endocrine Societies, 2022)
The presence of autoantibodies is a common link between autoimmune hypothyroidism (AH) and Systemic Lupus Erythematosus (SLE). The coexistence of AH (Hashimoto’s Thyroiditis) and SLE is common; however, massive pericardial effusion (PEEF) with signs of tamponade is extremely rare and only a few cases have been reported in literature. We present a case of a 54-year-old female who came in with progressive dyspnea who was found out to have massive PEEF from overt AH and concurrent SLE, which was successfully managed medically. This gave us valuable insight that massive pericardial effusion occurring in overt hypothyroidism may be secondarily caused by other co-existing disease entities such as SLE. The importance of the correct diagnosis cannot be overemphasized, as this largely contributed to the successful management of this case.